ФЕНОМЕН ЛІДЕРСТВА В ПОЛІТИЧНІЙ БОРОТЬБІ ЗА ДОБИ УКРАЇНСЬКОЇ РЕВОЛЮЦІЇ 191701920 РР. (Zaporizhzhia Historical Review, 2021)
The article reveals leadership role in 1917-1920 events in Ukraine. Peculiarities of Ukrainian political elite in liberation period are shown, compared with Polish, Czech and Finnish elites. Conclusion is drawn that lack of strong leaders among Ukrainian politicians was one of the most important defeat reasons of Ukrainian national-democratic revolution.